2006
DOI: 10.1007/s10439-006-9139-z
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Copolymers Prevent Aggregation of Heat Denatured Lysozyme

Abstract: We investigated the ability of certain triblock copolymer surfactant poloxamers of the form polyethylene oxide-polypropylene oxide-polyethylene oxide (PEO-PPO-PEO), to prevent formation of stable aggregates of heat denatured hen egg lysozyme. Differential scanning calorimetry (DSC) and synchrotron small angle x-ray scattering (SAXS) experiments were performed to study the thermodynamics and solution structures of lysozyme at temperatures between 20 and 90°C in the presence and absence of poloxamers with variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Pluronics are believed to be absorbed to the abnormally exposed hydrophobic regions of the unfolded proteins, alter local hydrophobic interactions as well as alter the local surface tension in such a fashion to facilitate protein disaggregation and refolding. 42 In all systems, PEG-polyHis was more effective in preventing insulin aggregation than F-127. Modest results with F-127 to protect insulin at the interface may be explained on the basis of anomalous behavior of PEG chains at the water-MC interface.…”
Section: Discussionmentioning
confidence: 91%
“…Pluronics are believed to be absorbed to the abnormally exposed hydrophobic regions of the unfolded proteins, alter local hydrophobic interactions as well as alter the local surface tension in such a fashion to facilitate protein disaggregation and refolding. 42 In all systems, PEG-polyHis was more effective in preventing insulin aggregation than F-127. Modest results with F-127 to protect insulin at the interface may be explained on the basis of anomalous behavior of PEG chains at the water-MC interface.…”
Section: Discussionmentioning
confidence: 91%
“…[3] Because similar forces drive protein aggregation, we hypothesized that P188 also behaved as a synthetic chaperone. Previous investigations have shown that P188 interfered with heat-induced aggregation of lysozyme, [4,5] and subsequent work showed that Macromol. Biosci.…”
Section: Introductionmentioning
confidence: 99%
“…Mustafi et al found that amphiphilic, surfactant, multi‐block copolymers, such as Poloxamer 108 (P108), Poloxamer 188 (P188), and Tetronic 1107 (T1107) are efficient as additives to suppress aggregation of and to facilitate refolding of heat‐denatured hen egg white lysozyme (HEWL) and bovine serum albumin (BSA) in solution. Additionally, Lee et al demonstrated that poloxamers are more efficient than PEG in preventing aggregation of heat denaturized lysozyme. These findings indicate that copolymer surfactants may be applied to the treatment of burns and other conditions resulting in the denaturation of proteins.…”
Section: Mode Of Action Of Surfactants In Wound Healingmentioning
confidence: 99%